Animal Welfare of Rodents in Laboratory Research: Applications and Challenges of the 3Rs - , Elton Santos Guedes de Morais; , Vinícius Antonio Barbosa Gonçalves; , Millena Patrício do Nascimento Ferreira; , Alline de Paula Reis; , Anisio Francisco Soares (Archives of Current Research International, 2025)
Animal models, particularly rodents, are indispensable in biomedical research due to their physiological and genetic similarities to humans, enabling advancements in understanding diseases, developing therapies, and ensuring safety in drug testing. Rats and mice have been extensively utilized in diverse fields such as neuroscience, endocrinology, cardiovascular research, and toxicology, owing to their adaptability, rapid reproductive cycles, and cost-effectiveness. However, the ethical implications of animal research needs a balanced approach that prioritizes animal welfare while advancing scientific knowledge. The Three Rs (3Rs) principle — Replacement, Reduction, and Refinement—provides a framework for minimizing animal use, refining experimental conditions to reduce suffering, and exploring alternative methods. This review examines the advantages and limitations of laboratory rodents in scientific research through the lens of the 3Rs, highlighting their recent contributions to fields such as renal disease, pharmacology, toxicology, and regenerative medicine. Additionally, it explores emerging alternatives, including in vitro models, organ-on-a-chip systems, and computational approaches, which aim to reduce reliance on animal models while maintaining scientific rigor. By integrating ethical considerations with innovative methodologies, this review underscores the importance of advancing both animal welfare and biomedical research.